From past patterns to future preparedness: a secondary analysis of the Global Burden of Disease Study 2021 on neonatal communicable disease burden in China and the Asia-Pacific region, 1990–2035 - Guo, Chuchu; Zhang, Liang; Cheng, Rui; Wang, Xu; Sun, Yanqun (Translational Pediatrics, 2026)
Communicable diseases (CDs) is the leading cause of death among neonates worldwide, and achieving the Sustainable Development Goal (SDG) 3.2 target (ending preventable neonatal deaths) relies on evidence-based analysis of CDs burden trends and risk factors. This study aims to analyze the temporal trends of CDs burden among neonates in China and the Asia-Pacific region from 1990 to 2021 [based on the Global Burden of Disease (GBD) 2021 database], and project future to 2035, to provide targeted evidence for neonatal health interventions.